Hubungan usia dan jenis kelamin dengan derajat keparahan stroke hemoragik berdasarkan volume hematoma dan lokasi perdarahan supratentorial pada Computed Tomography (CT) scan kepala - Rizky Aulia Wulandari; Muhamad Yunus; Rinto Hadiarto; Alfi Wahyudi (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Hemorrhagic stroke has a very high mortality and disability rate. According to the World Stroke Organization, there will be 11.9 million new cases of stroke and 7 million deaths annually by 2025. Hemorrhagic stroke accounts for 28.8% of stroke cases globally and approximately 32.9% in Indonesia. Age and gender are known to play a role in the epidemiology of hemorrhagic stroke, but their relationship to severity based on hematoma volume and supratentorial hemorrhage location remains understudied. Purpose: To determine the relationship between gender and age and hemorrhagic stroke severity based on hematoma volume and supratentorial hemorrhage location on head CT scans at Dr. H. Abdul Moeloek Regional General Hospital (RSUD) from 2022 to 2025. Method: This analytical observational study used a retrospective cross-sectional approach, involving 71 participants using a total sampling technique. The study found that the largest age group was 45-65 years old (24 patients (33.8%), and 36 patients were male (50.7%). Hematoma volumes <30 ml were found in 51 patients (71.8%), and deep cerebral hemorrhage in 49 patients (69.0%). Results: The chi-square test showed no association between gender and age with hematoma volume or supraterritorial bleeding location (p>0.05). Conclusion: There was no association between gender and age with hemorrhagic stroke severity based on head CT scans.   Keywords: Age; Head CT Scan; Hemorrhagic Stroke; Hematoma Volume; Sex.